Price Discovery from Offer Price to Opening Price of Initial Public Offerings - Aggarwal, Reena; Wu, Yanbin (Journal of Financial and Quantitative Analysis, 2025)
Abstract We examine the preopening process and price discovery from the offer price to the first open price in initial public offerings. The extent of price discovery during preopening is influenced by firm characteristics and preopening attributes, such as volume of shares executed in preopening, canceled orders, order imbalance, and changes in indicative price. Institutional investors cancel 4 orders for every executed order. Each phase of preopening contributes to incremental price discovery. In “hot” IPOs, almost all price discovery processes occur during preopening, whereas in “cold” IPOs, half of the price adjustment occurs after the market opens.